1997
DOI: 10.1002/art.1780400716
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 receptor promotion of multinucleated giant cell formation by human monocytes. A mechanism for methotrexate‐induced nodulosis in rheumatoid arthritis

Abstract: Objective. To determine why methotrexate (MTX) exacerbates rheumatoid nodules in some patients, despite the effective suppression of synovial inflammation. Methods. Phorbol myristate acetate (PMA)‐induced differentiation of monocytes into multinucleated giant cells was used as an in vitro model to study the effects of adenosine on nodulosis. Results. MTX at 200‐2,000 nM or the adenosine A1 agonist N5‐cyclopentyl adenosine (CPA) (10−12 to 10‐9 M) or the A2 antagonist 3,7‐dimethyl‐1‐propargylxanthine markedly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
1
40
0
5
Order By: Relevance
“…Previous studies have demonstrated a role for adenosine and adenosine A 1 R in regulating formation of multinucleated giant cells from peripheral blood monocytes [45][46][47], a finding consistent with the observations here. Similarly, in preliminary studies, we have observed that both DPCPX and rolofylline block osteoclast formation from human bone marrow-derived precursors (He, Mazumder and Cronstein, unpublished observations).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated a role for adenosine and adenosine A 1 R in regulating formation of multinucleated giant cells from peripheral blood monocytes [45][46][47], a finding consistent with the observations here. Similarly, in preliminary studies, we have observed that both DPCPX and rolofylline block osteoclast formation from human bone marrow-derived precursors (He, Mazumder and Cronstein, unpublished observations).…”
Section: Discussionsupporting
confidence: 92%
“…Altogether, these findings suggest that GM-CSF promotion of multinucleated MA requires P2X 7 purinergic signaling carried out through the release of ATP and its conversion into adenosine, which mediates MA fusion. In support of this, adenosine has been reported to promote the formation of multinucleated giant cell by human monocytes (68). In addition, lung inflammation resulting from elevated adenosine in adenosine deaminase-deficient mice is characterized by accumulation of multinucleated giant MA (69).…”
Section: Discussionmentioning
confidence: 90%
“…1). Adenosine influences monocyte maturation also by promoting the formation of multinucleated giant cells via A 1 receptor stimulation, whereas A 2 receptor activation prevents the generation of giant cells (Merrill et al, 1997; Fig. 1).…”
Section: Effect Of Adenosine On Monocyte/macrophage Maturation and Prmentioning
confidence: 99%